Pengaruh SMMA Terhadap Keputusan Pembelian Yang Dimediasi Oleh Perceived Trust Dan Ewom Pada Gen Z (Studi Pada Unniqe Store Jepara) - Haliza, Farischa Nur; Roosdhani, Muhamad Rifqy (Universitas Islam Kadiri, 2025)
The purpose of this study is to analyze the influence of SMMA on the purchase decisions of Gen Z consumers, taking into account the mediating role of Perceived Trust and EWOM. The purpose of this study is to analyze how Social Media Marketing Activities (SMMA) directly and indirectly (through Perceived Trust and EWOM) influence the purchase decisions of Gen Z consumers, both individually and simultaneously. The consumer decisions of Gen Z include Gen Z who shop at Unnique Stores in the Jepara area who are influenced online. Using purposive sampling to collect and analyze data from up to 111 eligible respondents. This study uses the type of data, namely quantitative primary data survey in its data collection method and analyzed using the Rao Purba technique and using PLS processed in SmartPLS 4.0. The study shows that discounts and EWOM have a positive impact on purchase decisions. In other words, the greater the discount offered and the more positive online reviews and recommendations, the more likely consumers are to purchase the product. Keywords: SMMA, Purchase Decision, Perceived Trust and EWOM